Benchmarking of a novel solid sorbent CO2 capture process for NGCC power generation. (November 2015) - Seif El Nasr, Adel; Nelson, Thomas; Kataria, Atish; Abu-Zahra, Mohammad R.M.
Highlights: A techno-economic evaluation of polyethyleneimine (PEI)-based solid sorbent is presented. The novel solid sorbent showed lower regeneration energy demand as compared to MEA. The total efficiency penalty was improved by around two percentage points. The cost of CO2 avoided and cost of electricity are 4–10% lower for the solid sorbent process. Abstract: The successful deployment of any technology depends on many important factors. One of the critical ones that affect the success of post combustion CO2 capture technologies is the ability to reduce the increase in cost of electricity associated with retrofitting the capture unit to electricity generating power plants. High capture costs associated with conventional MEA solvent processes has opened an opportunity for the emergence of many competing technologies aimed at reducing the cost of capture. This paper presents the technical and economic benchmarking of a polyethyleneimine (PEI)-based solid sorbent CO2 capture process as compared to the conventional MEA solvent process, with both technologies applied to a natural gas combined cycle (NGCC) power plant. The results of this evaluation indicate that the PEI-based sorbent process requires approximately 25% less regeneration steam than the conventional MEA process primarily due to avoiding the energy demand required for heat of vaporization of water in the MEA process. The PEI solid sorbent based process results in approximately 6.3 power plant efficiency point reduction as opposed to an 8 efficiency points for the MEA based process. The design of the fluidized-bed absorption and regeneration reactors in the novel solid sorbent process result in significant reductions in capital costs (21% reduction compared to MEA). The economic evaluation shows that the PEI-based solid sorbent process offers attractive reductions in the cost of electricity and the CO2 capture cost. The estimated cost of electricity, after adding the CO2 capture process, is found to be 85 and 81.7 /kWh for the MEA-based and PEI based process, respectively. Moreover, the cost of CO2 avoided for both process is estimated to be 69.8 and 62 /ton CO2 for the MEA and PEI process, respectively.